An adaptive method to solve multilevel multiobjective linear programming problems - Mustapha Kaci; Radjef, Sonia (arXiv.org, 2022)
This paper is a follow-up to a previous work where we defined and generated the set of all the possible compromises of multilevel multiobjective linear programming problems (ML-MOLPP). In this paper, we introduce a new algorithm to solve ML-MOLPP in which the adaptive method of linear programming is nested. First, we start by generating the set of all the possible compromises (set of all non-dominated solutions). After that, an algorithm based on the adaptive method of linear programming is developed to select the best compromise among all the possible compromises achieved. Finally, all the construction stages are carefully checked and illustrated with a numerical example.